ANTIMICROBIAL EFFECT OF DIFFERENT ETHANOLIC EXTRACTS OF PROPOLIS AGAINST METHICILLIN-RESISTANT STAPHYLOCOCCUS SPP ISOLATES - W. Albino-Táutiva; Y. Bernal-Rosas; D. Pardo-Mora; F. Cruz-Uribe; O. Torres-García (Journal of Animal and Plant Sciences, 2017)
The emergence of multidrug-resistant bacteria has now become a critical issue in both human and veterinary medicine, and in this way, the antibiotic treatment for the control of these infections has become ineffective. In the current investigation, we studied the antimicrobial effectiveness of five ethanolic extracts of propolis (EEP) from different regions of Colombia against six strains of Staphylococcus spp. methicillin-resistant. The analysis of major compounds of propolis showed the presence of diterpenicacids, prenylated benzophenones, and triterpenes in the propolis obtained from Cundinamarca Antioquia, and Huila regions respectively. Minimum inhibitory concentration (MIC) technique was implemented to evaluate the antibacterial activity of the propolis extracts. Was found that all propolis extracts showed inhibitory action against the Staphylococcus strains evaluated MIC90 = 60 – 30 mg/mL, and the average MICs (mg/mL) for each EEP were: EEP1 = 11.88±4.98; EEP2 = 31.25±16.71; EEP3 = 51.25±21.43; EEP4 = 22.81±11.88; EEP5 = 17.50±10.25. EEP displayed varying effectiveness against six Staphylococcus spp isolates strains, with minimal bactericidal concentration (MBC) within the range from 1.87 to 30 mg/mL. In conclusion, the extract's antimicrobial effectiveness depends on the origin of propolis and the evaluated Staphylococcus spp isolates. Also, these findings suggest that the propolis extracts could be an alternative method to control multidrug-resistant infections caused by Staphylococcus spp.
Keywords: Antibiotic resistance; Antimicrobial; Methicillin; Propolis; Staphylococcus spp